Exploring Language Variation and Dialectology on the Perspective Sociolinguistic - Ratu, Aisyah (LIER: Language Inquiry & Exploration Review, 2024)
Purpose: This have a look at explores language variant and dialectology via a sociolinguistic lens, focusing on factors which includes age, gender, and linguistic behavior. Subjects and Methods: Using a complete technique together with descriptive information, paired-samples t-checks, regression analysis, ANCOVA, and Pearson correlation, the studies investigate the difficult dynamics of language use inside numerous populations. Results: Findings screen massive differences in language utilization patterns based totally on age and gender, with older people tending to speak fewer phrases in step with day in comparison to more youthful individuals. Regression analysis suggests that age performs a slightly good-sized function in predicting linguistic variation. Furthermore, ANCOVA results highlight the importance of considering covariates consisting of age whilst studying organization differences in language usage. The Pearson correlation analysis indicates a terrible correlation between age and phrases spoken in step with day. Conclusions: Overall, this observe contributes to a deeper knowledge of language version and sociolinguistic dynamics, with implications for future research exploring the interaction between language, identity, and social factors.